(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, metals have different properties, some of which are soft. and elastic, and some are hard, flexible, or brittle. Metallic Properties of metals for selecting suitable materials for manufacturing products. Introduction: Metals (Latin: metallum; Ancient Greek: metallon - I dig, or I dig from the ground) - high electrical conductivity under normal conditions, hot conductivity, electrical conductivity, good conductance of electromagnetic waves Simple substances with specific properties such as reflectivity and plasticity. Metals in the solid state have a crystalline structure. In the vapor state, it is monatomic.